Ulama dalam Perang Kemerdekaan di Minangkabau: Studi Maklumat Perang Sabil 1945-1948 - Putri, Bintang Maharani; Hardi, Etmi (Lembaga Yasin AlSys, 2024)
This research was motivated by the lack of public knowledge regarding the role and participation of Minang ulama against the aggressors during the 1945-1948 revolution. The purpose of the research was to find out how the role of the ulama in spreading the sabil war idiology, convincing readers and listeners to obey the call for sabil war and how the impact of these edicts was received by the people. The urgency of the research is to find out whether the sabil war idiology has been embedded for a long time in the Minang society through the role of the ulama so that the call for sabil war edicts has become important to the community. This research uses the critical historical method, consisting of four stages (1) heuristics as an activity to collect data traces of the past, (2) source criticism, (3) interpretation and (4) historiography as an activity of reconstruction or writing historical studies based on data that has been obtained into a work of history. The results showed that the chain of struggle of the ulama in Minang against the Dutch had started from the historical record of the Padri War period. The dynamics of the ulama's struggle in providing strength against the colonial in Minangkabau reached its accumulation point with the issuance of the ulama's decision on 27 July 1947, resulting in a call for jihad in sabil war. Through the call and invitation of the ulama, the war was sacred and sanctified. With the spread of the sabil war idiology, the ulama played a role in trying to arouse the spirit of the people.